Dynamic event-triggered control of networked control systems with uncertainty and transmission delay. Issue 1 (January 2022) - Zhu, Xunlin; Zhang, Xiuxiu; Wei, Jumei; Du, Haiping; Xi, Jiangtao
Abstract: This paper presents a method for designing dynamic event-triggered controller of networked control systems (NCSs) with uncertainty and time delays. Under the condition that the Lyapunov function of the system is allowed to increase at each jump point, the globally exponentially stable (GES) of the system can be achieved by using the Riccati differential equation and the principle of average dwell time (ADT). The minimum allowable inter-event interval is obtained by limiting the increment of the Lyapunov function within the transmission interval. Both the static event triggering and no transmission delay are included in the designed dynamic event triggering mechanism as special cases. A numerical example is given to verify the correctness and validity of the proposed method.